Professional Engagement and Work Performance of Public Elementary School Teachers - Pillas, Carmela (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the professional engagement and work performance of public elementary school teachers in the Jalajala District, Schools Division Office of Rizal during the School Year 2025–2026. The research aimed to determine the extent of teachers’ professional engagement and its relationship to their work performance. The study population comprised 154 teachers from Bagumbong, Bayugo, Jalajala, Lubo, Pagkalinawan, Palaypalay, Punta, and Sipsipin Elementary Schools. Respondents were profiled based on age, sex, civil status, educational attainment, position title, length of service, in-service trainings attended, and membership in professional organizations.A descriptive survey research design with documentary analysis was employed. Data on professional engagement were gathered using a researcher-made questionnaire-checklist covering participation in professional development, collaboration and teamwork, adherence to professional standards, and involvement in school and community activities. Teachers’ work performance was assessed using results from the Individual Performance Commitment and Review (IPCR) for School Year 2024–2025.Findings revealed that the majority of respondents were female, married, aged 31 and above, holding Teacher I–III positions, and actively pursuing graduate education. Most had over ten years of service, participated in various trainings up to the international level, and belonged to multiple professional organizations. Teachers demonstrated high engagement in professional development, collaboration, adherence to standards, and school-community involvement. Significant differences in professional engagement were noted with respect to age, length of service, and in-service trainings attended, while sex, civil status, educational attainment, position title, and organizational memberships showed no significant impact. Work performance was generally rated as very satisfactory, with professional engagement significantly correlating with work performance.The study recommends recognition of outstanding teachers, targeted seminars and trainings, and implementation of a professional development plan to further enhance engagement and performance. Future studies may explore additional variables affecting teacher engagement and effectiveness.